Rosalía de Castro’s necrologic and elegiac spaces in Madrid and Galicia’s press - García Vega, Lucía (Madrygal. Revista de Estudios Gallegos, 2011)
This article aims to provide essential new information related to the death of Rosalía de Castro (1837-1885). Besides referring to the news published in newspapers from Madrid and Galicia, we recovered some texts by other writers who paid tribute to her in 1885.